The effect of motivational incentives on clients’ religious self-regulation in an institutionalized drug treatment program - Abdul Ghani, Mohamad Salleh; Lim Abdullah, Haslee Sharil (Human Resource Management Academic Research Society, 2022)
Performing religious and spiritual activities is known to have a positive effect on substance use treatment and rehabilitation. Thus, this study aimed to examine the effect of motivational incentives in motivating clients to perform religious activities in a Narcotic Treatment and Rehabilitation Centre, also known as PUSPEN in Malaysia. A true experimental study was conducted involving the randomization of participants into the experimental groups that received tangible incentives for performing compulsory religious activities and the controlled groups that doesn’t receive any incentive. A total of 44 clients were selected as participants based on the inclusion criteria set by the researcher. The participants were assessed by their achievement in memorizing surahs as well as adherence to religious programs and activities in the PUSPEN within 12 weeks of study. A total of seven surahs and three extra surahs were targeted to be memorized by the participants throughout the study period. For the experimental group, participants were given incentives for each successful surah memorized. Meanwhile, for the control group, no form of incentive was given to the participants. CM rewards are in the form of stickers with a monetary value of RM5.00 each which can be used to exchange for items within the PUSPEN. Pre-test analysis to obtain baseline data was done prior to the study session and the post-test analysis was done after week-12 of study. Participants were gathered after one month the study ended for the follow-up test using the same instrument. The Religious Self-Regulated Questionnaire (SRQ-R) which have been translated into the Malay language and adapted into the Islamic version was used to examine the level of religious self-regulation during pre, post and follow-up test. The findings showed that there are no significant differences between the experimental group and the control group on the client's level of religious self-regulated in pre, post and follow-up tests. CM incentives helped improve the performance of the clients in memorizing surahs but did not significantly affect the clients’ motivation in performing religious activities during rehabilitation in the PUSPEN. The implementation of CM in the psycho-spiritual aspect in the PUSPEN environment is still considered as new and inconclusive. Future researchers can improve the study by increasing the sample size and uses higher incentives values to obtain a more accurate and comprehensive findings on the effectiveness of CM intervention on religious self-regulation.